Chapter 6 'Doing family' online Translocality, connectivity, and affection - Lexander, Kristin Vold (Taylor & Francis, 2023)
This chapter studies the ways in which family members draw on their mediational repertoires to interact with one another near and far in the light of theories of translocality (Conradson & McKay 2007, Kytölä 2016), family discourse practices (Tannen et al. 2007) and language and emotions (Pavlenko 2004, Dewaele 2010). Through the analysis of digital power and connection manoeuvres (cf. Kendall 2006, Tannen 2006, Tannen et al. 2007) and morality practices (Ochs & Kremer-Sadlik 2007), the chapter shows how their interactional practices differ between local and transnational digital connectivity as well as between regular and occasional family contacts. The expressions of affection in these mediated interactions are examined to identify how they differ by the various types of local to global connectivity in the data and to conclude on how the diversity of linguistic repertoires becomes a resource to articulate emotions between adults, parents and their children.